2019
DOI: 10.1177/2325967118821875
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of PROMIS CAT Administration in the Ambulatory Sports Medicine Clinic With Respect to Cost and Patient Compliance: A Single-Surgeon Experience

Abstract: Background:Pay-for-performance reimbursement models are becoming increasingly popular, but the implementation of a routine patient-reported outcome (PRO) collection system places additional burden on both the patient and the provider. The Patient-Reported Outcomes Measurement Information System (PROMIS) was developed in an effort to make PRO collection more practical and efficient, but providers may be reluctant to embrace a transition to a PROMIS-based clinical outcome registry.Hypothesis:PROMIS can be succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
1
23
1
Order By: Relevance
“… 39 , 40 , 41 Additionally, multiple studies in the literature have emerged to support the use of the PIF CAT as an important augmentation to capturing physical function in patients with pain. 27 , 34 , 42 Kendall et al. 43 correlated the PIF CAT with the PF CAT in a population of patients presenting with spinal pain and concluded that the PIF CAT is a useful augmentation to physical function measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 , 40 , 41 Additionally, multiple studies in the literature have emerged to support the use of the PIF CAT as an important augmentation to capturing physical function in patients with pain. 27 , 34 , 42 Kendall et al. 43 correlated the PIF CAT with the PF CAT in a population of patients presenting with spinal pain and concluded that the PIF CAT is a useful augmentation to physical function measures.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 23 , 24 , 25 , 26 As PROMIS measures continue to be introduced in new orthopedic disciplines, continued evaluation in specific patient populations before widespread adoption is essential. 27 , 28 , 29 , 30 Although the performance of the PROMIS PF CAT has previously been examined in meniscal surgery, 31 the comparative performance of the PF CAT relative to gold standard function PROMs has yet to be established. 31 Furthermore, the performance of PROMIS PIF and Depression has yet to be established in meniscal surgery.…”
mentioning
confidence: 99%
“…One recent study estimated the total cost of administration to be approximately $1,000 per month. 24 Fees and other implicit costs are important to acknowledge as these could be significant hurdles for researchers to overcome. While baseline and operative variables were assessed for statistical significance, only 3 variables were observed to have statistically significant differences among the 2 subgroups (e.g., sex, obesity, length of hospital stay).…”
Section: Discussionmentioning
confidence: 99%
“…However, other costs such as server fees, tablets to administer the surveys and research assistants to analyze the data add additional costs. One recent study estimated the total cost of administration to be approximately $1,000 per month [ 24 ]. Fees and other implicit costs are important to acknowledge as these could be significant hurdles for researchers to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the feasibility and compliance of our system. On average, patients take 3.29 minutes to complete the entire survey set 5 and only have to answer 15.3 PROMIS questions in total 6 . Patient compliance for in-clinic survey administration is over 90%, 6 with remote e-mail compliance approaching 70% (unpublished data, P. Borowsky, November 2018).…”
Section: Discussionmentioning
confidence: 99%